(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the image of Stepan Razin in V. M. Shukshin’s novel "I have come to give you Free Rein" as an artistic embodiment of the ideals of the Cossacks. The article analyzes how Shukshin reveals the features of Cossack freedom, the desire for justice and popular protest through the figure of Razin, creating a multifaceted image of a hero who opposes oppression and fights for freedom. Special attention is paid to the philosophical and ethical aspect of Razin’s controversial personality, whose desire for the liberation of the people turns into a tragedy. The study highlights the importance of Razin’s image for understanding national identity and spiritual search in Russian literature of the twentieth century.